Hamlet Live: the 7 I's Experiential Strategy Framework for heritage visitor attractions. Issue 2 (4th March 2022) - Lund, Niels Frederik; Holst-Beck, Peter; Pine II, B. Joseph; Leask, Anna
ABSTRACT: In an increasingly competitive market for tourist destinations, visitor attractions play a key role in enticing visitors to the destination, and as such must continually develop new extraordinary experiential offerings to keep visitors coming. The Renaissance castle of Kronborg, a Danish heritage visitor attraction and the setting of Shakespeare's Hamlet, has shown the way by staging Hamlet Live, an interactive theatrical experience. Its success is due to the professional actors' co-creative performances and improvisations. In this study, based on observations, semi-structured interviews and thematic analysis of TripAdvisor reviews, we identify and describe seven interconnected elements that have made Hamlet Live successful in terms of revenue and visitor satisfaction. These elements form an experiential strategy framework that other heritage visitor attractions could use to create extraordinary experiences. We provide recommendations on which types of heritage visitor attractions could replicate the achievements of Kronborg's Hamlet Live .